Why Do Consumers Adopt NFC Keychains? The Role of Trust and Usefulness in Digital Payment Adoption - Regina Humaningtyas Purba; Adnan Kasofi; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
This study investigates why consumers adopt NFC keychains as a digital payment tool by examining the role of trust and perceived usefulness within an extended Technology Acceptance Model. Using a quantitative approach with non-probability convenience sampling, 235 valid responses were analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that perceived trust and perceived usefulness significantly influence behavioral intention. These results indicate that consumer adoption of NFC keychains is primarily driven by trust in the system and perceived practical benefits rather than usability or security considerations. The study contributes to the digital payment literature by highlighting the shifting determinants of adoption in intuitive, institutionally regulated payment innovations.